Strengthening Mechanisms in Nickel-Copper Alloys: A Review - Olexandra Marenych; Andrii Kostryzhev (Metals, 2020)
Nickel-Copper (Ni-Cu) alloys exhibit simultaneously high strength and toughness, excellent corrosion resistance, and may show good wear resistance. Therefore, they are widely used in the chemical, oil, and marine industries for manufacturing of various components of equipment, such as: drill collars, pumps, valves, impellers, fixtures, pipes, and, particularly, propeller shafts of marine vessels. Processing technology includes bar forging, plate and tube rolling, wire drawing followed by heat treatment (for certain alloy compositions). Growing demand for properties improvement at a reduced cost initiate developments of new alloy chemistries and processing technologies, which require a revision of the microstructure-properties relationship. This work is dedicate to analysis of publicly available data for the microstructure, mechanical properties and strengthening mechanisms in Ni-Cu alloys. The effects of composition (Ti, Al, Mn, Cr, Mo, Co contents) and heat treatment on grain refinement, solid solution, precipitation strengthening, and work hardening are discussed.